Hubungan Pengetahuan dan Sikap Pedagang terhadap Penggunaan Siklamat pada Minuman Boba yang Dijual di Aplikasi Online Wilayah Surabaya Timur - Virghina Bintang Pininfarina; Trias Mahmudiono (Media Gizi Kesmas, 2023)
Background: The use of food additives in a product is one of the producers' efforts to reduce production prices. Excessive use of food additives can harm consumers in terms of health. One of the food additives used is artificial sweetener, cyclamate. Excessive use of sodium cyclamate can cause health problems, such as insomnia, allergies, irritation, hypertension, diarrhea, etc. With good knowledge and attitude, food producers can produce healthy products and not harm their consumers. Boba drink is one of the most popular drinks toda, but the sweet taste makes this drink suspected that uses artificial sweeteners.   Objectives: Analyze the correlation between knowledge and attitude of seller with the use of cyclamate in boba drinks sold in the online applications in East Surabaya region. Methods: This research was analytical observational with a cross-sectional study design. This study used all boba drink sellers in online applications in the East Surabaya Region as the population. Sample determination using a simple random sampling technique, total 48 samples of productions. The samples obtained had been tested for deposition at the Nutrition Laboratory of FKM UNAIR. Samples that had positive results will be followed by quantitative tests at the BBLK Surabaya. The results performed univariate and bivariate analysis, and presented in the form of data processing table. Results: 6 samples contained cyclamate (<10mg/kg), classified as safe. Majority level of knowledge "less” (54.2%) and positive attitude (93.8%). No correlation between knowledge of sellers and the use of cyclamate in boba drinks (p-value= 0.286). No correlation between the attitude of sellers and the use of cyclamate in boba drinks (p-value= 0.286). Conclusions: No correlation between the knowledge and attitudes with the use of cyclamates in boba drinks sold using online applications in the East Surabaya Region.